Variant achalasia, the hole of the original classification - Huh, Joon Young; Park, Moo In; Park, Seun Ja; Moon, Won; Kim, Hyung Hun (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: High-resolution manometry (HRM) is a useful tool for classifying esophageal motility disorders. However, there remain findings that cannot be classified in clinical fields. Recently, an updated classification system was announced. The purpose of this study was to evaluate whether originally unclassifiable groups can now be classified according to the updated Chicago Classification system. Materials and Methods: We reviewed the results of HRM studies performed from January 2008 to December 2010 on 150 consecutive patients (75 men, age 17-76) referred to the Gospel Hospital manometry laboratory for evaluation. We found originally unclassified results and re-categorized them according to the updated Chicago Classification system. Results: Thirty-seven of 150 patients were originally unclassified cases. Patients from the unclassified and classified groups had similar distributions of age and sex. All unclassified patients were re-diagnosed as having variant achalasia according to the updated Chicago Classification system. Conclusion: The updated Chicago Classification can categorize originally unclassified groups of esophageal motility disorder.